2016
DOI: 10.1007/s00408-016-9916-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Single Nucleotide Polymorphisms of PADI4 and HLA-DRB1 Alleles with Susceptibility to Rheumatoid Arthritis-Related Lung Diseases

Abstract: PADI4 polymorphisms and HLA-DRB1 alleles could attribute differently to the development of airway abnormalities and ILD, respectively, in RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
(46 reference statements)
0
7
1
Order By: Relevance
“…Likewise, each SE allele may differ in their roles in RA-ILD development although their roles in ACPA positive RA development are quite in the same direction. Recently, Song et al explored polymorphisms in PADI4 and HLA-DRB1 in RA patients and found that recessive genotype of padi4_92 was associated with airway abnormalities and that tryptophan at position 9 of HLA-DRB1 amino acid sequence was strongly associated with RA-ILD in Korean patients with an odds ratio (OR) of 22.89 [ 43 ].…”
Section: Lung Involvement In Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, each SE allele may differ in their roles in RA-ILD development although their roles in ACPA positive RA development are quite in the same direction. Recently, Song et al explored polymorphisms in PADI4 and HLA-DRB1 in RA patients and found that recessive genotype of padi4_92 was associated with airway abnormalities and that tryptophan at position 9 of HLA-DRB1 amino acid sequence was strongly associated with RA-ILD in Korean patients with an odds ratio (OR) of 22.89 [ 43 ].…”
Section: Lung Involvement In Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…HLA-DQB1 ∗ 03:01 and HLA-DQB1 ∗ 06:01 were found as susceptibility alleles for BE in RA [ 41 , 61 ]. A polymorphism in PADI4 (recessive genotype of padi4_92) was reported to associate with the airway abnormalities in RA [ 43 ]. A small study showed that 16% of RA patients with diffuse BE were heterozygous for the delta F508 mutation of the cystic fibrosis transmembrane conductance regulator gene (CFTR) regardless of sweat chloride concentration or nasal potential difference measurements [ 62 ].…”
Section: Lung Involvement In Rheumatoid Arthritis (Ra)mentioning
confidence: 99%
“…The most definite function of PADI4 in human diseases is the close relationship between PADI4 gene polymorphisms and rheumatoid arthritis (RA) risk [45][46][47][48][49]. In addition, high levels of PADI4 protein are expressed in the inflamed synovium of RA patients [50][51][52][53][54][55][56].…”
Section: Padi4 and Rheumatoid Arthritismentioning
confidence: 99%
“…Among the known isoforms of PADIs [ 6 ], PADI2 and PADI4 have been previously associated with RA pathogenesis [ 7 ]. PADI4 polymorphisms leading to higher enzyme levels have been associated with RA susceptibility and HRCT abnormalities in lungs [ 8 ]. PADI4 is mainly expressed in macrophages, neutrophils, and eosinophils and triggers neutrophil extracellular traps (NETs) formation [ 9 ], whereas PADI2 is highly expressed in macrophages [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%